Insight into the denitrification mechanism of Bacillus subtilis JD-014 and its application potential in bioremediation of nitrogen wastewater. (April 2021) - Yang, Ting; Yang, Qian; Shi, Yi; Xin, Yu; Zhang, Liang; Gu, Zhenghua; Shi, Guiyang
Graphical abstract: Highlights: The feasibility of nitrogen removal performance in real system of B. subtilis JD-014 was confirmed. Nine unconventional denitrification genes were screened and identified. High similarity in genome was found between JD-014 and denitrification functional lacking strain, B. subtilis 168. Abstract: Bacillus is a species that has been suggested to contain abundant denitrifying strains. The aerobic denitrifying Bacillus subtilis JD-014 isolated previously was found to exhibit efficient nitrogen removal capability with outstanding tolerance to nitrite toxicity. However, the bioremediation potential in real treatment process has not been verified. Meanwhile, although several functional denitrifying genes have been screened, the comprehensive mechanism of denitrification pathway for JD-014 remains unclear. Herein, a lab-scale continuous experiment was conducted to investigate the application potential of JD-014, which demonstrated that JD-014 could effectively deplete nitrogen pollution, with the maximum removal efficiency of NO3 − -N and NO2 − -N of 98.91 % and 81.99 %, respectively. Furthermore, the complete genome analysis of JD-014 revealed the denitrification pathways in genetic levels. 43 putative genes are associated with the nitrogen pathways, among which 9 selective putative genes were validated to participate in the denitrification process. The present work suggests that JD-014 has great potential of practical application in bioremediation of nitrogen wastewater. The understanding of nitrogen metabolic pathways also provides significant molecular information for further Bacillus species modification and development.